Antioxidant responses following active and passive smoking of tobacco and electronic cigarettes. (23rd July 2016) - Poulianiti, Konstantina; Karatzaferi, Christina; Flouris, Andreas D.; Fatouros, Ioannis G.; Koutedakis, Yiannis; Jamurtas, Athanasios Z.
Abstract: Context: It has been indicated that acute active and passive tobacco cigarette smoking may cause changes on redox status balance that may result in significant pathologies. However, no study has evaluated the effects of active and passive e-cigarette smoking on redox status of consumers. Objective: To examine the acute effects of active and passive e-cigarette and tobacco cigarette smoking on selected redox status markers. Methods: Using a randomized single-blind crossover design, 30 participants (15 smokers and 15 nonsmokers) were exposed to three different experimental conditions. Smokers underwent a control session, an active tobacco cigarette smoking session (smoked 2 cigarettes within 30-min) and an active e-cigarette smoking session (smoked a pre-determined number of puffs within 30-min using a liquid with 11 ng/ml nicotine). Similarly, nonsmokers underwent a control session, a passive tobacco cigarette smoking session (exposure of 1 h to 23 ± 1 ppm of CO in a 60 m 3 environmental chamber) and a passive e-cigarette smoking session (exposure of 1 h to air enriched with pre- determined number of puffs in a 60 m 3 environmental chamber). Total antioxidant capacity (TAC), catalase activity (CAT) and reduced glutathione (GSH) were assessed in participants' blood prior to, immediately after, and 1-h post-exposure. Results: TAC, CAT and GSH remained similar to baseline levels immediately after and 1-h-post exposure ( p  > 0.05) in all trials. Conclusions: Tobacco and e-cigarette smoking exposure do not acutely alter the response of the antioxidant system, neither under active nor passive smoking conditions. Overall, there is not distinction between tobacco and e-cigarette active and passive smoking effects on specific redox status indices.